In the beginning : Secretary-General Trygve Lie and the establishment of the United Nations - Ravndal, Ellen Jenny, 1984- (Bristol University Press, 2023)
This book reviews the formative years of the United Nations (UN) under its first Secretary-General Trygve Lie.